Beyond Knowledge: The Moderating Role of Investment Literacy in Biases and Irrational Investment Decision-Making - Wahyu Febri Ramadhan Sudirman; Rinda Fithriyana; Mohd Winario; Nana Sari; Puji Ananda Irvan (Journal of Economics, Entrepreneurship, Management Business and Accounting, 2026)
Purpose – This study investigates irrational investment behavior among individual stock investors in the Indonesian capital market, with particular attention to the role of investment literacy. Grounded in behavioral finance theory, the research examines how cognitive biases—namely availability bias, overconfidence bias, and herding bias are associated with irrational investment decision-making and assesses whether investment literacy moderates these relationships. As an additional analysis, the study also explores potential gender differences in the proposed relationships. Design/methodology/approach – This study employed a quantitative research design and utilized Partial Least Squares Structural Equation Modeling (PLS-SEM) to examine the relationships among the proposed constructs and test the moderating effects. Data were collected from 756 Indonesian stock investors through structured online and offline questionnaires. CMB preventive strategies were implemented to reduce the risk of common method bias (CMB). Findings – The results show that while investing literacy was inversely correlated with irrational investment decision-making, availability bias, overconfidence bias, and herding prejudice were favorably correlated. Additionally, the association between availability bias and irrational investment decision-making was considerably mitigated by investment literacy; a lesser relationship between availability bias and irrational investment decision-making was linked to higher levels of investment literacy. The associations between herding bias and overconfidence bias, however, were not substantially mitigated by financial literacy. There were no discernible variations between male and female investors in the structural linkages analyzed, according to the supplementary Multi-Group Analysis (MGA), indicating that the observed associations function equally across gender groups. Originality/Value – This study adds to the body of research on behavioral finance by showing that investment literacy plays a crucial boundary condition in the relationship between availability bias and irrational investment decision-making, but it has no discernible moderating effect in the relationships between herding bias and overconfidence bias. The study offers a more comprehensive understanding of the circumstances in which financial knowledge is linked to lower levels of irrational investment decision-making by incorporating cognitive biases, objective investment literacy, and an additional gender-based comparison within an emerging market setting